1992
DOI: 10.1103/physrevb.46.2764
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics, structural stability, and phase transitions in incommensurate and commensurateA2BX4

Abstract: Numerous materials with the general formula A2BX4, where A and B are cations and X is the anion, are isomorphous to Il-K2SO4 (space group Pnam) at high temperatures. A considerable number of them exhibit a structural instability leading to an incommensurately modulated phase with identical superspace symmetry. K&Se04 is the archetypical example. From the analysis of the incommensurate structures, the polarization vector of the unstable frozen mode can be determined, being similar in all investigated compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…This view is consistent with the explanation provided for the incommensurate lattice instabil- ity exhibited by several of these compounds at ambient pressure. [13][14][15]26 It was found that the presence of large anionic BX 4 groups in relation to the size of the A cations induces increased stresses in the backbone lattice resulting in an incommensurate modulation and strict loss of translational periodicity along a particular crystallographic axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is consistent with the explanation provided for the incommensurate lattice instabil- ity exhibited by several of these compounds at ambient pressure. [13][14][15]26 It was found that the presence of large anionic BX 4 groups in relation to the size of the A cations induces increased stresses in the backbone lattice resulting in an incommensurate modulation and strict loss of translational periodicity along a particular crystallographic axis.…”
Section: Discussionmentioning
confidence: 99%
“…They consist of anionic BX 4 tetrahedral groups which are separated from each other by interstitial A cations. [11][12][13][14][15][16] The essential way in which these systems differ from each other is via the ratios of the sizes of the anionic BX 4 tetrahedral units to that of their interstitial A cations (ZnCl 4 /K ϩ ϭ1.69, ZnBr 4 / Rb ϩ ϭ1.62, ZnCl 4 /Rb ϩ ϭ1.52, ZnBr 4 /Cs ϩ ϭ1.43, ZnCl 4 /Cs ϩ ϭ1.35, SeO 4 /K ϩ ϭ1.23). Therefore we can directly examine the importance of this size ratio in influencing crystalline to noncrystalline transitions within this family.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, a softening of the optic phonon branch with AE 2 symmetry has been found in K 2 SeO 4 . Landau theory did lead to a symmetry of the a* modulation equal to the AE 2 normal mode also and the superstructures of Rb 2 ZnCl 4 , Rb 2 ZnBr 4 and K 2 ZnCl 4 have been found to form according to this mode (Etxebarria et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 This size criterion should also be responsible for the existence of the incommensurate lattice instability in the A 2 BX 4 compounds. This phenomenon is in agreement with the hypothesis that the ordered phase is due to the softening of modes that were soft in the prototypic hexagonal high-temperature phase.…”
Section: Discussionmentioning
confidence: 99%